Modelling the dispersion of early life stages of blackspot seabream in the Strait of Gibraltar - Sammartino, Simone; Sánchez-Garrido, José Carlos; García-Lafuente, Jesús; Naranjo-Rosa, Cristina Belén; Hidalgo, Manuel; Gil Herrera, Juan (FAO, 2018)
The blackspot seabream (Pagellus bogaraveo) is a commercially appreciated demersal fish, widespread in the North-eastern Atlantic and middle-western Mediterranean. The Strait of Gibraltar is an important fishing area where artisanal fleets from Spain and Morocco target this species using special longline gears known as “voracera”. Different assessments of the state of health of this species point to the same result: a clear overexploitation of the resource with no specific/joint management implemented yet. There is some agreement in literature in considering the Strait of Gibraltar as a specially energetic and dispersive spawning zone for this species. After the spawning, eggs and larvae (early life stages [ELS]) would be scattered to both sides of the Strait of Gibraltar, mostly to the breeding area close to Estepona, where high concentrations of juveniles occur. A high resolution hydrodynamic model coupled to a 3D Lagrangian particle tracking system is employed to assess the potential dispersal pathways of blackspot seabream ELS spawned in the Strait of Gibraltar. Recursive releases of passive tracers in virtual spawning spots in this zone are tracked under different conditions of tidal current, including fortnightly modulation, in order to obtain the spatial dispersion patterns of the studied species. Semidiurnal variability appears as a fundamental factor for horizontal dispersion and vertical displacement of the spawning products, determining the trajectories of the ripening ELS of the species.
Keywords: Pesca; Dinámica; Oceanografía